Analisis Hukum Terhadap Kewenangan Penyelenggaraan Pendidikan Layanan Khusus di Provinsi Papua - Bauw, Lily (Penerbit Yayasan Daarul Huda Kruengmane, 2022)
This research is in the preparation of a study regarding Legal Analysis of the Authority to Provide Special Education Services in Papua Province, which is a new breakthrough to answer the needs of the indigenous Papuan community in order to develop human resources in Papua. This study is a model that is the basis for the executive and legislative parties in following up on the implementation of education in Papua Province. In this study, the foundations, studies and findings that support the need to design an educational development model in Papua Province have been explained. Thus, it is hoped that this input can be responded to by the executive and legislative parties in Papua Province to realize a regional policy in advancing the education sector that is pro-people. Hopefully the policies that will be prepared in the future will be a form of commitment by the regional government and the Papuan People's Representative Council (DPRP) to provide affirmative action in the field of education for indigenous Papuans who live in areas with difficult access or remote and very remote areas. There is great hope that with educational programs that truly provide convenience to the indigenous Papuan people, human resources in Papua Province will increase and be able to compete.